2018
DOI: 10.1002/anie.201807775
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of Tertiary Boronic Esters by Conjunctive Cross‐Coupling

Abstract: Catalytic enantioselective conjunctive cross-coupling has been developed to construct tertiary alkylboronic esters. These reactions occur with good yield and enantioselectivity for a range of substrates. Mechanistic experiments reveal aspects of the catalytic cycle that allow hindered substrates to react without significant complicating side reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 66 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…3j,5ab We recently reported that a variety of prochiral and chiral β,γ-unsaturated phosphonates possessing a trisubstituted alkene, one that bears only alkyl substituents, are excellent substrates for CAHB (Figure 4). 5a For example, 13 undergoes efficient catalyst-controlled diastereoselective CAHB. The use of ( R , R )- T2 leads to the formation of (2 R ,5 S )- 14 (82%, 97:3 dr); ( S , S )- T2 affords (2 S ,5 S )- 14 (81%, 98:2 dr).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3j,5ab We recently reported that a variety of prochiral and chiral β,γ-unsaturated phosphonates possessing a trisubstituted alkene, one that bears only alkyl substituents, are excellent substrates for CAHB (Figure 4). 5a For example, 13 undergoes efficient catalyst-controlled diastereoselective CAHB. The use of ( R , R )- T2 leads to the formation of (2 R ,5 S )- 14 (82%, 97:3 dr); ( S , S )- T2 affords (2 S ,5 S )- 14 (81%, 98:2 dr).…”
Section: Resultsmentioning
confidence: 99%
“…We have been exploring rhodium-catalyzed, directed-catalytic asymmetric hydroborations (CAHB) of functionalized alkene substrates with the goal of obtaining multifunctional, chiral boronic ester synthons. 4,5ab We find that several factors influence the regio- and stereochemical outcomes of these reactions; the nature of the directing group, the alkene substitution pattern, the nature of the alkene substituent and the nature of the chiral ligand each play pivotal roles. Using the TADDOL-derived phosphite T1 in combination with a common Rh(I) catalyst-precursor, the amide- and oxime ether-directed CAHB of β-aryl substituted methylidene substrates 1 and 3 result in boration at the less substituted terminus of the alkene affording γ-borylated products ( S )- 2 (71%, 96.5:3.5 er) and ( R )- 4 (70%, 95:5 er), respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conjunctive cross‐coupling reactions involving diphosphine palladium complexes appear to occur by a low‐barrier metal‐induced metallate shift followed by reductive elimination . Because the vinylidene insertion operates with an alternate Pd complex than previously described couplings, it was of interest to learn about this new reaction pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Conjunctive cross-coupling reactions involving diphosphine palladium complexes appear to occur by a low-barrier metal-induced metallate shift followed by reductive elimination. 26 Because the vinylidene insertion operates with an alternate Pd complex than previously described couplings, it was of interest to learn about this new reaction pathway. Analysis of the reaction was conducted by DFT (see Scheme 4 for description of method) and employed a complex between (η 3 -allyl)Pd(PCy 3 ) and the ‘ate’ complex as a starting point ( I-1 , the pathway involving a bis(phosphine)Pd(η 1 -allyl) is much higher in energy).…”
mentioning
confidence: 99%